2022
DOI: 10.1111/jpy.13277
|View full text |Cite
|
Sign up to set email alerts
|

Morphological plasticity in response to salinity change in the euryhaline diatom Pleurosira laevis (Bacillariophyta)

Abstract: Pleurosira laevis is a salt-tolerant diatom distributed around the world. The valve of P. laevis has distinct structures called ocelli, which are sharply defined areas with fine, densely packed pores. Two formae of this diatom, P. laevis f. laevis and P. laevis f. polymorpha, are distinguished from each other by their flat or dome-shaped valve faces and degree of elevation of the ocelli, respectively. In this study, we established 4 strains of P. laevis isolated from freshwaters or coastal areas in Japan and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 62 publications
0
10
2
Order By: Relevance
“…More genes encoding chaperones, heat shock proteins, and heat shock factors were downregulated than up-regulated (Figure S7b). Although we did not see significant differences in growth rates and apparent cellular stress in Pleurosira laevis between salinity 2 and 7 in culture experiments (Kamakura et al, 2022), the cells appear to be sensitive to the variations in stress levels between the conditions.…”
Section: Stress-responsive Gene Expressioncontrasting
confidence: 77%
See 4 more Smart Citations
“…More genes encoding chaperones, heat shock proteins, and heat shock factors were downregulated than up-regulated (Figure S7b). Although we did not see significant differences in growth rates and apparent cellular stress in Pleurosira laevis between salinity 2 and 7 in culture experiments (Kamakura et al, 2022), the cells appear to be sensitive to the variations in stress levels between the conditions.…”
Section: Stress-responsive Gene Expressioncontrasting
confidence: 77%
“…The association between osmotic pressure and valve morphology has been supported by studies in Skeletonema species (Balzano et al, 2011;Paasche et al, 1975) and Pleurosira laevis (Kamakura et al, 2022). Kamakura et al (2022) showed that P. laevis changed its valve morphology in response to the environmental osmotic pressure. Pleurosira laevis formed a flat valve face at salinity 2, whereas it formed a dome-shaped valve face at salinity 7.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations